Freestanding HRP–GOx redox buckypaper as an oxygen-reducing biocathode for biofuel cell applications1. Issue 7 (1st July 2015) - Elouarzaki, K.; Bourourou, M.; Holzinger, M.; Le Goff, A.; Marks, R. S.; Cosnier, S.
<x xml:space="preserve">Abstract</x> Horseradish peroxidase and glucose oxidase were immobilized on redox buckypapers modified by poly(pyrrole-concanavalin) for the electroreduction of oxygen into water.